2000
DOI: 10.1590/s1517-83822000000100016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different chemical agents in rapid decontamination of gutta-percha cones

Abstract: The effectiveness of seven disinfectant compounds used in dentistry for a rapid decontamination of 32 guttapercha cones adhered with Staphylococcus aureus, Enterococcus faecalis, Escherichia coli strains or Bacillus subtilis spores was compared. Cones were treated with 2% glutaraldehyde, 1% sodium hypochlorite, 70% ethyl alcohol, 1% and 0.3% iodine alcohol, 2% chlorhexidine, 6% hydrogen peroxide, and 10% polyvinylpyrrolidone-iodine, for 1, 5, 10, and 15 minutes. After treatment, each cone was transferred to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 8 publications
4
23
0
14
Order By: Relevance
“…The results of our study are consistent with those reported in other qualitative microbiological studies (6,33,35). Suchde et al (35) showed the effectiveness of a 1.5% chlorhexidine gluconate detergent solution (Savlon®) in decontaminating gpc in 30 seconds.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of our study are consistent with those reported in other qualitative microbiological studies (6,33,35). Suchde et al (35) showed the effectiveness of a 1.5% chlorhexidine gluconate detergent solution (Savlon®) in decontaminating gpc in 30 seconds.…”
Section: Discussionsupporting
confidence: 92%
“…Stabholz et al (33), demonstrated that 2% chlorhexidine in an aqueous solution effectively disinfects gpc contaminated with bacteria from the oral flora (Streptococcus mutans and Streptococcus sanguis), intestinal flora (Escherichia coli and Enterococcus faecalis), skin flora (Staphylococcus aureus), and environment (Bacillus subtilis), within 10 min. A qualitative bacteriological study carried out in our laboratory showed that a 2% chlorhexidine digluconate detergent solution eliminated in 1 (6). On the other hand, Siqueira et al (31) reported that a 2% chlorhexidine digluconate solution showed no sporicidal activity after 10 min of contact with gpc contaminated with spores of Bacillus subtilis (ATCC 19659).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…1 Owing to the thermoplastic characteristic of gutta-percha cones, they may not be sterilized by the conventional process in which moist or dry heat is used, because this may cause alteration to the gutta-percha structure. 2,3,4,6,8,10 For this reason, previous studies suggested that several different chemical agents could be used for the rapid decontamination of gutta-percha cones in dentistry.…”
Section: Introductionmentioning
confidence: 99%